Global competitiveness and capital flows: does stage of economic development and risk rating matter?* - Athari, Seyed Alireza; Shaeri, Komeil; Kirikkaleli, Dervis; Ertugrul, Hasan Murat; Ozun, Alper (Routledge Journals, Taylor & Francis Ltd, 2020)
This paper closes a gap in the relevant literature by investigating the role of a country's competitiveness on international capital mobility using robust panel multiple regressions with fixed and random effects. In this study, we use the Global Competitiveness Index to measure a country's competitiveness level. The research empirically investigates the effect of competitiveness on cross-border capital flows, and shows how stages of economic development and country-specific risk ratings influence inflows and outflows of capital under the effect of competitiveness. Overall, we found that competitiveness has a positive and statistically significant impact on aggregated and disaggregated capital flows. However, the magnitude of its impact varies over different stages of development and across country risk levels.
Keywords: Competitiveness; capital flows; stages of economic development; country risk